2014
DOI: 10.1095/biolreprod.113.115261
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Expression of Musashi-1 and Musashi-2 RNA-Binding Proteins During Spermatogenesis: Analysis of the Deleterious Effects of Dysregulated Expression1

Abstract: Spermatogenesis is a complex developmental process whereby diploid spermatogenic stem cells become haploid and undergo a series of morphological changes to produce physically mature spermatozoa. Crucial to this process are a number of RNA-binding proteins, responsible for the posttranscriptional control of essential mRNAs and particularly pertinent to the two periods of inactive transcription that occur in spermatogenesis. One such group of RNA-binding proteins is the Musashi family, specifically Musashi-1 (MS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
49
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(53 citation statements)
references
References 70 publications
4
49
0
Order By: Relevance
“…This was followed by additional studies showing roles for the Musashi proteins in regulating normal cell differentiation and organ development for other tissue types (5,1115), emphasizing the essential nature of this protein signaling over great evolutionary distance. For example, in early studies in mice, Msi1 was found to be highly expressed in the brain, and Msi1 deficiency caused hydrocephaly (16).…”
Section: Introductionmentioning
confidence: 98%
“…This was followed by additional studies showing roles for the Musashi proteins in regulating normal cell differentiation and organ development for other tissue types (5,1115), emphasizing the essential nature of this protein signaling over great evolutionary distance. For example, in early studies in mice, Msi1 was found to be highly expressed in the brain, and Msi1 deficiency caused hydrocephaly (16).…”
Section: Introductionmentioning
confidence: 98%
“…9 More recent studies showed that Msi2 may have a unique role that is required for normal spermatogenesis, with Msi2 overexpression resulting in male sterility in vivo. 10 Apart from being a cell development regulator, Msi2 is also linked to carcinogenesis and tumor progression. Recent studies have shown that Msi2 is a mediator of proliferation and differentiation in myeloid malignancies, 9 and its knockdown leads to cell cycle arrest and cell apoptosis in acute myeloid leukemia (AML).…”
mentioning
confidence: 99%
“…Both have two RNA-recognition motifs, das Chagas and Baroni contributed equally to this work. [15][16][17][18][19] In germ cells, however, both, can influence translational modulation during the differentiation and maintenance of maturation of these cells [20][21][22] and any dysregulation can lead to cellular dysfunctions promoting tissue instability, as well as the onset of tumor progression. The RRM1 of MSI1 protein contains 20-110 amino acid residues and RRM2 contains amino acid residues.…”
Section: Introduction: the Rna Binding-protein Musashimentioning
confidence: 99%